An Airlift Perfusion Bioreactor for Tissue Engineering Applications: from Computational Modeling to Experimental Validation - Elisa Capuana; Camilla Carbone; Francesco Carfi Pavia; Giulio Ghersi; Vincenzo La Carrubba; Valerio Brucato (Chemical Engineering Transactions, 2024)
Tissue engineering (TE) offers promising solutions for regenerative medicine through the use of porous scaffolds and cells, providing a favorable environment for the production of functional three-dimensional (3D) tissues. However, TE strategies have faced physiological limitations with static three-dimensional culture alone, and perfusion bioreactors provide a controlled environment that better mimics native tissue. In this study, we present the optimized geometry of an existing custom-made perfusion bioreactor that utilizes an external airlift circulation loop, essentially a specially structured bubble column designed for the simultaneous allocation of multiple seeded scaffolds. By reducing volumes and materials, the optimized system maintains the same level of reliability and functionality. The study employs computational fluid dynamics (CFD) analysis and a mathematical model to gain insights into fluid flow and oxygen transport, respectively. Therefore, in line with the increasingly recognized trend of device miniaturization, scaling down the initial device would enable high-speed analysis of cellular response in perfused cultures, allowing the study of various morphologies, different cell populations, or different drug treatments. Furthermore, the possibility of creating series and parallel connections between multiple devices, while maintaining dimensions suitable for incubator insertion, demonstrates the potential of this system for testing engineered constructs while simultaneously enabling time and cost reduction compared to existing perfusion devices in the field of Tissue Engineering.